(untitled) (Research, Society and Development, 2021)
The frequent use of chemical synthesis fertilizers leads to serious environmental problems, this implies the use of nutritional alternatives to optimize the production of coffee in the nursery, so the use of plant growth-promoting bacteria could be an interesting alternative to stimulate development. of the coffee tree. The objective of this work was to evaluate the inoculation of five strains of rhizobia during the process of obtaining seedlings of Coffea arabica cv. Isla 5-15 grafted on the Coffea canephora cv. Robusta pattern enlivened under natural shade, in relation to two controls. Two inoculations were carried out, one in the seeds before the sowing of the seeds of both cultivars and another at the time that the hypocotyledonal graft was carried out, through imbibition for one hour and thirty minutes respectively. Germination percentage was evaluated; seedling height, stem diameter and number of true leaves, starting 30 days after transplantation and monthly up to 150 days. At the end of the experimental period, the fresh and dry root and foliar mass were evaluated, the slenderness and Dickson indices were determined. The inoculated seeds and grafts originated seedlings that showed significant differences and surpassed the results shown by the two controls used for all the variables evaluated. These results suggest the use of rhizobia strains for the production of coffee seedlings in the context of sustainable agriculture.